Peningkatan kreativitas dan inovasi Pamong Desa melalui Pelatihan Manajamen Arsip Elektronik - Diah Kusuma, Chusnu Syarifa; Rusdiyanto, Wahyu; Nugroho, Fajar Wahyu (Universitas Negeri Yogyakarta, 2024)
The aim of this Community Service (PPM) activity is to prevent loss and damage to records at the sub-district office in Ketawang Village, Grabag District, Magelang Regency and to improve the ability of village administrators to manage computer-based records. To achieve this goal, the method used in this activity was training for Ketawang Village officials. Ketawang Village was chosen as the target of this training activity, considering that this village is an economically/socially unproductive village, but provides basic public services needed by village communities which can result in very high levels of damage and loss of archives. The training was held at the office in Ketawang Village on 17-18 July 2023. The result was that PPM participants' understanding had increased regarding the differences between manual and electronic archives, digital archives, electronic archive management practices, creation and practice of electronic archive systems after the PPM was held.